Diffuse dermal angiomatosis of the breast. Issue 2 (2nd April 2020) - Nguyen, Nicholas; Silfvast-Kaiser, Annika S.; Frieder, Jillian; Zaayman, Marcus; Menter, Alan
Abstract: Diffuse dermal angiomatosis of the breast can be a painful, irritating, and persistent inflammatory condition. It tends to present in middle age and is associated with a number of risk factors, mainly relating to tissue hypoxia. There are no standard treatment guidelines, and current treatment focuses on mitigating tissue hypoxia by addressing atherosclerosis through lifestyle changes and medical and/or surgical intervention. Herein, we present a case of diffuse dermal angiomatosis of the breast, describing the condition and current treatment approaches and the likelihood that this diagnosis is more common than previously believed.